Usability testing for user interface of Lembaga Zakat Selangor Portal / Suriani Muda - Muda, Suriani (2015)
There are challenges of services portal to attract users to used their portal and maintain the relationship with users. Therefore, the most important part to succeed is for the web designers to design a good and usable government portal. To design the government portal by using the correct user interface design guidelines in term of function and user. When the users browse the government portal, they found many problems such as there is no button to make the payment after the "zakat pendapatan" calculation. The target government portal for this study is Lembaga Zakat Selangor portal. Web designers should understand the needs of users and designing the user interface in accordance with user requirements that based on usability evaluation. Since there is an increase in internet and World Wide Web users, it is important that good user interface is developed by web designers. The objectives in this study are to identify the problems of.user interface in LZS portal and to propose new user interface design for LZS portal. The usability assessment results by this study can be used as reference for future interface design for government portal. In the end of this study was proposed new user interface design for Lembaga Zakat Selangor portal. The scope of this study is focus on calculation and makes payment for "zakat pendapatan". Data are gathered using eye tracking method and questionnaire among employee that pay "zakat pendapatan" and working in Selangor. An eye tracking study was conducted to evaluate interface design for Lembaga Zakat Selangor portal. Participants need to complete three tasks on the portal. The results was shows a number of usability problems faced by the participants throughout the evaluation session which can be categorized into ten usability heuristic. Hence, from these findings web designers should look at the issues seriously before designing the services portal site. The issues such as web designers should do usability evaluation of user interface for user requirements before implement the portal. From feedback by the users, web designers can do correction for user interface design for better improvement.